The cicadas (Hemiptera: Cicadoidea: Cicadidae) of Madagascar including a new tribe, five new genera, twelve new species, four new species synonymies, five revised species status, ten new combinations, new tribal assignments for four genera, one new subtribe synonymy, a checklist and key to the species - Sanborn, Allen F. (Zootaxa, 2021)
The known cicada fauna of Madagascar is identified. Yanga mahajangaensis n. sp., Nelbroma betrokaensis n. gen., n. sp., Trismarcha parva n. sp., Abroma bezamahafalyensis n. sp., Abroma falcata n. sp., Timbaltransversa pronotosigillata n. gen., n. sp., Malagasia argentea n. sp., Malagasia italivianaensis n. sp., Malagasia rubrastragala n. sp., Deremeces andringitraensis n. gen., n. sp., Malgachialna rubracosta n. sp., and Cephalalna tulearensis n. sp. are described as new. The genera Mouldspsaltria n. gen., and Orientafroinsularis n. gen. are described as new with the reassignment of Mouldspsaltria madegassa (Boulard, 1996) n. comb., Orientafroinsularis elenae n. comb., rev. stat., Orientafroinsularis hova (Distant, 1905b) n. comb., Orientafroinsularis loici (Boulard, 2000) n. comb., Orientafroinsularis martini (Distant, 1905b) n. comb., Orientafroinsularis matilei (Boulard, 2000) n. comb., Orientafroinsularis nigrans (Distant, 1904) n. comb., Orientafroinsularis pulverulenta (Distant, 1905b) n. comb., Orientafroinsularis seychellica (Dmitriev, 2020) n. comb., rev. stat., and Orientafroinsularis seychellensis (Boulard, 1999) n. comb., rev. stat. to these new genera. Yanga argyrea (Melichar, 1896) rev. stat. is removed from subspecies status of Yanga pulverea (Distant, 1882) and returned to species rank. Antankaria pulverulenta madegassa Boulard, 1999 n. syn. and Chremistica pulverulenta madagascariensis Boulard, 2001 n. syn. are considered synonyms of Orientafroinsularis pulverulenta (Distant, 1905b) n. comb. eliminating the potential homonym based on “madagascariensis”. Antankaria pulverulenta seychellensis Boulard, 1999 and Chremistica pulverulenta seychellensis Boulard, 2001 n. syn. are considered synonyms, elevated to species rank and reassigned to the new genus to become Orientafroinsularis seychellensis (Boulard, 1999) n. comb., rev. stat. Chremistica elenae elenae Boulard, 2001 rev. stat. is shown to be a synonym of Chremistica elenae madagascariensis Boulard, 2001 n. syn. and is a distinct species from Chremistica elenae seychellica Dmitriev, 2020 rev. stat. with both elevated to species rank and transferred to the new genus to become Orientafroinsularis elenae (Boulard, 2001) n. comb., rev. stat. and Orientafroinsularis seychellica (Dmitriev, 2020) n. comb., rev. stat. Antankariini n. tribe is formed for former Malagasy members of the Cryptotympanini Handlirsch, 1925. Four genera are reassigned to Malagasiini Moulds & Marshall, 2018, Anopercalna Boulard, 2008 from Taphurini Distant, 1905d, Cephalalna Boulard, 2006a from Chlorocystini Distant, 1905c, Malgotilia Boulard, 1980b from Parnisini Distant, 1905c and Viettealna Boulard, 1980a from Lamotialnini Boulard, 1976. There are no remaining members of Chlorocystini or Taphurini in Madagascar after the generic reassignments and these tribes are removed from the Madagascar fauna. Anopercalnina Boulard, 2008 n. syn. is made a junior synonym to Malagasiini Moulds & Marshall, 2018. An updated faunal list is provided to summarize recent changes to the assignment of taxa. The currently known cicada fauna of Madagascar is comprised of 65 species from 25 genera, eight tribes and three subfamilies.